Nikah Siri Online dalam Perspektif Hermeneutika Hukum Islam: Analisis Teks, Konteks, dan Implikasi Sosial - Mohammad Taufiq Jatmiko; Isnatin Ulfah (Fakultas Syariah Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
This article examines the rise of the practice of online marital as a contemporary legal and social phenomenon that challenges the Islamic family legal framework in Indonesia. The main problem in this study is the insynchronization between classical fiqh texts built in a socio-physical context and modern digital reality, where marriage contracts are carried out virtually through bold platforms. This research aims to reinterpret the principles of marriage law, especially related to guardians, witnesses, and the validity of contracts through the hermeneutic approach of Gadamer and Ricoeur. The research method used is normative qualitative by integrating textual analysis of jurisprudence, regulations, and recent court decisions with a hermeneutic approach. The findings of the study show that online serial marriage poses significant legal risks, especially in terms of guardianship verification, witness validity, and certainty of the legal status of women and children. Hermeneutic analysis shows that a reinterpretation of the context of classical legal texts is necessary to safeguard maqāṣid al-syarī'ah, in particular the protection of nasab, rights, and legal security. This study concludes that marriage registration by the state is not just administrative, but a legal mechanism needed to ensure justice and social protection in the digital era.